ASO-OKE: THE RELATIONSHIP BETWEEN THE CONSUMPTION OF ETHNIC CLOTHING AND NORMATIVE SOCIAL INFLUENCE - Ijioma, Nkechinyereamaka (2010)
This research paper presents an evaluation of consumers within and outside their ethnic country in relation to the consumption of ethnic clothing. This was achieved by investigating how consumers behaved in the presence of normative social influence. The reason for this study is due to the increased interest researchers have, in studying ethnic minorities and their consumption of ethnic related products. However, little attention has been paid to the consumption behaviour of consumers within their ethnic countries. The effect of globalisation has led to a growth of interrelationship between countries, which has not only made the economy better, but also changed the ways people choose to consume ethnic oriented products in today’s society. This research found that consumers either within or outside their ethnic countries know the relevance of using ethnic related products. However, it does not determine their consumption, except it is of normative importance. When there is a need to conform to traditional standards, consumers would choose to use ethnic products regardless of their personal social values. It was also discovered that this attitude was significant to both young and middle aged adult consumers. The findings of this study contribute further to the understanding of normative social influence.